2021
DOI: 10.7759/cureus.16575
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Clinical Symptoms With Nasal Endoscopy and Radiological Findings in the Diagnosis of Chronic Rhinosinusitis: A Prospective Observational Study

Abstract: Baba Caliaperoumal et al. This is an open access article distributed under the terms of the Creative Commons Attribution License CC-BY 4.0., which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 28 publications
(41 reference statements)
2
3
0
Order By: Relevance
“…In this study male to female ratio was 1:1.23 with female preponderance which corresponds to study carried out by Baba Caliaperoumal et al [13] where the male to female ratio was 1:1.18. However, most studies have higher male to female ratios like in a study done by Srivastava et al [14] where male to female ratio was 1.38:1.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In this study male to female ratio was 1:1.23 with female preponderance which corresponds to study carried out by Baba Caliaperoumal et al [13] where the male to female ratio was 1:1.18. However, most studies have higher male to female ratios like in a study done by Srivastava et al [14] where male to female ratio was 1.38:1.…”
Section: Discussionsupporting
confidence: 89%
“…Many studies have shown that the correlation between CT scan and DNE findings was very high [15,21,22] . Other studies [13,17] also showed significant correlation between symptom-based criteria and DNE scores and CT scan scores.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…However, our study findings were at variance to findings of Caliaperoumal et al (2021) in which female preponderance was observed and mean age was also higher. 4 In present study, four cardinal features were noted in majority of cases either on unilateral or bilateral sites. The most common cardinal clinical feature observed in our study was nasal obstruction (94.9%), followed by nasal discharge (61%), hyposmia/ anosmia/ parosmia in 43.2% and facial pain in 29.7% cases.…”
Section: Discussionsupporting
confidence: 55%
“…The role of epithelial cells in the pathogenesis of CRS has attracted more and more attention. As the first natural barrier to contact external stimuli and an important structure of innate immunity, epithelial cells on the surface of nasal mucosa play an important role in protecting the body from external harmful factors [10][11][12] . Once the epithelial cell barrier function is damaged, it is mainly manifested in epithelial cell abscission and dysfunction in CRS, which will provide conditions for the invasion of external harmful substances, such as bacteria, virus invasion and allergen exposure, so as to cause and aggravate the chronic inflammation of nasal cavity and paranasal sinus mucus membrane and lead to the accumulation of inflammatory cells and inflammatory factors [13,14] .…”
mentioning
confidence: 99%